Socioeconomic profile of users and reasons why they seek dental care in teaching clinics - Fabiana Barros Marinho Maia Fabiana; Emer son Tavares de Sousa; Vanessa Feitosa Alves; Fábio Correia Sampaio; Franklin Delano Soares Forte (Editorial Ciencias Médicas, 2016)
Introduction: educational institutions are in charge of training qualified professional personnel who must be prepared to act in society. Objective: describe the socioeconomic profile of dental clinic users and identify the reasons why they make use of the service. Methods: a cross-sectional quantitative study was conducted of clinical cariology records from a higher education institution. 313 records were analyzed in the years 2011-2013. The data collected were sociodemographic variables (age, sex, family income, parents' schooling level) and reasons why they seek care. Data were treated descriptively and subjected to chi-square statistical tests, where 5 % was considered significant. Results: users' mean age was 6 ± 7.81 years with an even distribution between the sexes: female 50.2 % and male 49.8 %. Most parents had attended school for more than eight years: fathers 67.35 % and mothers 70.43 %. Around 37.75 % of the fathers and 43.9 % of the mothers with more than eight years of schooling go to the clinic for treatment, whereas 29.6 % of the fathers and 26.53 % of the mothers seek preventive care. The relationship found between education and reasons why parents seek care was p= 0.01. As to family income, 49.9 % reported that the family did not receive any, 39.8 % receive minimum wages and 10.4 % get more than one paycheck. Among no-income families, 37 % attend the service in search of treatment and 12.7 % seek preventive care. Conclusion: the population seeking care at the clinic was the most vulnerable socioeconomically and the reason for attending consultation was treatment.